65-jähriges Jubiläum von Ludwig Karničar - Kocher, Gernot (Slavia Centralis, 2020)
65th Anniversary of Ludwig Karničar
Keywords: Ludwig Karničar; anniversary; Slavic studies; celebrations; life and work